IL‐4 downregulates expression of the target receptor CD30 in neoplastic canine mast cells. (9th August 2016) - Bauer, K.; Hadzijusufovic, E.; Cerny‐Reiterer, S.; Hoermann, G.; Reifinger, M.; Pirker, A.; Valent, P.; Willmann, M.
Abstract: CD30 is a novel therapeutic target in human mast cell (MC) neoplasms. In this 'comparative oncology' study, we examined CD30 expression and regulation in neoplastic canine MC using a panel of immunomodulatory cytokines [interleukin‐2 (IL‐2), IL‐4, IL‐5, IL‐6, IL‐13 and stem cell factor (SCF)] and the canine mastocytoma cell lines NI‐1 and C2. Of all cytokines tested IL‐4 was found to downregulate expression of CD30 in NI‐1 and C2 cells. We also found that the CD30‐targeting antibody‐conjugate brentuximab vedotin induces growth inhibition and apoptosis in both MC lines. Next, we asked whether IL‐4‐induced downregulation of CD30 interferes with brentuximab vedotin‐effects. Indeed, pre‐incubation of NI‐1 cells with IL‐4 decreased responsiveness towards brentuximab vedotin. To overcome IL‐4‐mediated resistance, we applied drug combinations and found that brentuximab vedotin synergizes with the Kit‐targeting drugs masitinib and PKC412 in inhibiting growth of NI‐1 and C2 cells. In summary, CD30 is a new marker and IL‐4‐regulated target in neoplastic canine MC.